Longitudinal evaluation of cognitive functioning in pediatric multiple sclerosis: report from the US Pediatric Multiple Sclerosis Network. (October 2014) - Charvet, LE; O'Donnell, EH; Belman, AL; Chitnis, T; Ness, JM; Parrish, J; Patterson, M; Rodriguez, M; Waubant, E; Weinstock-Guttman, B; Krupp, LB; ,
Background: Approximately one-third of those with pediatric-onset multiple sclerosis (MS) experience cognitive impairment. Less is known concerning their change in cognitive functioning over time. Objective: Changes in cognitive function over time were measured in the largest pediatric cohort to date through the US Network of Pediatric MS Centers. Methods: A total of 67 individuals with pediatric MS ( n =62) or clinically isolated syndrome (CIS, n =5), ranging from 8–17 years of age (mean age±standard deviation (SD)=14.37±2.02) completed initial and follow-up neuropsychological testing after an average of 1.64±0.63 years apart. The nine tests administered measure general intellect, attention and working memory, verbal memory, visuomotor integration, language, and executive functioning. Results: Rate of impairment (having one-third or more scores in the impaired range) was 37% at baseline and 33% at follow-up. Tests commonly impaired were measures of visuomotor integration, speeded processing, and attention. Most tested did not decline over two years. There was no clear pattern of change on any specific measure. Conclusion: Findings suggest that, over short timeframes, stable or even improved performances on measures of cognitive ability can occur. Pediatric MS may instead prevent expected age-related cognitive gains.